Political Broker and Budget Mafia in Indonesian Parliament - Moh. Ilham A. Hamudy; Ahmad Imam M. Rais (Research and Development Agency Ministry of Home Affairs, 2014)
AbstractBudget mafia practices and brokerage phenomenon in ministries/agencies and the parliament in the country's financial dredge is very alarming. Not counted how much money is successfully robbed. The modus is varying, so it is not easy to dismantle. Because expert move, the law enforcers had trouble catching them. This article tried to describe the mode of action and often they do. The method is done by tracing the various reports in newspapers. From tracking and in-depth analysis it could be concluded that in order to minimize the action of brokers and budget mafia practices there are some necessary steps. First, fixing the finances system of political parties, reducing the dominance of parliament in budget management and election of public officials, and encourage law enforcement. Second, transparency debates the state budget in the parliament to be a key budget reforms. Third, the involvement of the community is also important to increase the transparency of the state budget discussions. AbstrakPraktik mafia anggaran dan fenomena broker di kementerian/lembaga dan parlemen yang mengeruk keuangan negara sangat memprihatinkan. Tidak terhitung berapa banyak uang yang berhasil dirampok. Modusnya berbeda-beda, sehingga tidak mudah untuk membongkar. Saking ahlinya, para penegak hukum mengalami kesulitan menangkap mereka. Artikel ini mencoba untuk menjelaskan modus tindakan yang kerap mereka lakukan. Metode kajian dilakukan dengan menelusuri berbagai laporan di surat kabar. Dari pelacakan dan analisis mendalam itu dapat disimpulkan bahwa untuk meminimalkan aksi broker dan praktik mafia anggaran ada beberapa langkah yang diperlukan. Pertama, memperbaiki sistem keuangan partai politik, mengurangi dominasi parlemen dalam pengelolaan anggaran dan pemilihan pejabat publik, dan mendorong penegakan hukum. Kedua, transparansi dalam perdebatan penentuan anggaran negara di parlemen menjadi kunci bagi reformasi anggaran. Ketiga, keterlibatan masyarakat juga penting untuk meningkatkan transparansi pembahasan APBN.